KONSEP KEPALA KELUARGA ANTARA LAKI-LAKI DAN PEREMPUAN DALAM SURAT AN NISA (4) AYAT 34 - Kholis, Muhammad Nur (ISTINBATH JURNAL HUKUM, 2015)
AbstractHusbands role in the family is affected by the role of the wife. Harmonious domestic life is the desire of every couple who fostered by the head of the family both men and women. But in practice conditions many families are affected by the threat of hurricanes and the current inequality of a leadership role. The relationship between husband and wife at a given time can suffer shocks worrying. Tali marriage in Islam is a strong bond that is formed couples in order to reach the fabric of household. In al-Quran Allah characterization of his marriage with the term mitsaqan ghalizhan (rope solid agreement). This article attempts to explain the relationship between the holy book the Koran and the community, both of which are factors that have a dependency memenculkan different interpretations, particularly of the concept of "head of household". In other words, changes in the condition and development is a means to understand the scope of the meaning of al-Quran.Â Keyword: Quran , Society , head of the family , Sura An- Nisa ( 3 ) : 34 .Â AbstrakPeran suami dalam keluarga dipengaruhi oleh peran isteri. Kehidupan rumah tangga yang harmonis merupakan dambaan setiap pasangan suami istri yang dibina oleh kepala keluarga baik laki-laki maupun perempuan. NamunÂ  dalam prakteknya kondisi keluarga banyak dipengaruhi oleh ancaman badai dan arus ketimpangan peran kepemimpinan. Hubungan antara suami istri pada saat tertentu dapat mengalami guncangan yang mencemaskan. Tali pernikahan dalam Islam adalah sebuah ikatan yang kokoh yang menjalin pasangan suami istri dalam rangka menggapai jalinan rumah tangga. Dalam al-Qur`an Allah swt menyifati hubungan pernikahan itu dengan istilah mitsaqan ghalizhan (tali perjanjian yang kokoh). Artikel ini mencoba untuk menjelaskan hubungan antara kitab suci al-Qurâan dan masyarakat, yang keduanya merupakan faktor yang mempunyai ketergantungan yang memenculkan interpretasi berbeda, terutama dari konsep "kepala rumah tangga". Dengan kata lain, perubahan kondisi dan perkembangan merupakan sarana untuk memahami luasnya makna al-Qur`an.Â Keyword : Al-Qur`an, Masyarakat, kepala keluarga, QS An- Nisa ( 3 ) : 34.